Hemophilia with intracranial bleeding - A case report - Sunarto Sunarto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1995)
A hemophiliac boy was hospitalized due to head injury in the previous sixteen days. On admission the' consciousness decreased and visus of both eyes was 1/on. CT scan showed blood clot in the area of dorsomedial of medial cerebral arteria and sign of hydrocephalus. A surgical procedure could not be taken due to lack of facilities (antihemophilic factor supply and assay of factor VIII activity). The patient was given 6 cryoprecipitate everyday and supportive treatment as indicated. Fortunately the patient recovered, no neurologic complication occurred except the visus of the right eye that was still 1/oo and the hydrocephalus decreased.Key words : hemophilia - laboratory diagnostics - head injury - hydrocephalus and decreased visus - cryoprecipitate